Pengaruh Peran Kepala Sekolah dan Penggunaan Media Pembelajaran terhadap Motivasi Mengajar Guru di Sekolah SMP Negeri di Kecamatan Bula Kabupaten Seram Bagian Timur - Rochmawati, Nur; Ratumanan, T.G.; Rahabav, P. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine (1) the influence of the role of the principal on teaching motivation, (2) the effect of the use of instructional media on teacher teaching motivation, (3) the effect of the role of the principal and use of instructional media jointly on teacher teaching motivation in public junior high schools in the district of Bula, East Seram regency. This type of research is expost-facto using quantitative methods. Data collection was carried out using a questionnaire or a Likert distribution questionnaire. The population as well as the sample in this study were all 69 PNS/Non PNS school principals and teachers from 3(three) public junior high schools in Bula District, East Seram Regency. The results showed that: 1) the role of the school principal (X1) had an effect on teachers’ teaching motivation (Y) by 6.3% based on (R square) of 0.063, (2) The use of instructional media (X2) had an effect on teachers’ teaching motivation (Y) of 23.6% besed on (R square) of 0,236, and (3) the role of the school principal (X1) and the use of instructional media (X2) has an effect on teacher motivation (Y) of 23,7% based on (R square) of 0.237. Based on the results of the reseach conducted, the variabel of the role of the school principal and use of learning media should be increased in order to increase the motivation to teach teachers in public junior high schools in Bula District, East Seram Regency.